"Tunisian Islam, " Women's Rights, and the Limits of French Empire in Twentieth-Century North Africa. Issue 1 (31st March 2023) - Weideman, Julian
Abstract: European colonialism catalyzed a proliferation of arguments linking national territories to allegedly distinctive forms of Islam. I consider "Tunisian Islam" under the French protectorate in Tunisia (1881–1956), a case that allows scholars not simply to track the formation of an orientalist discourse but to reveal the histories that the discourse has elided. This analysis has spatial and temporal parameters. First, the geographies of Muslim scholarship in colonial Tunisia exceeded both the national boundaries and the territory of the French empire. Above all, Muslim intellectuals in Tunisia under French rule pursued a multidirectional exchange with their colleagues in Egypt and the wider Middle East. This transnational context reveals the singular Tunisian Islam to be a specious construction. Second, colonial ideas about so-called Tunisian Islam were far from durable. Independence in 1956 led to a significant rupture as personal status legislation of the Tunisian Republic reconceived Tunisian Islam and created a new "invented tradition." Crucially, the Tunisian state fused national Islam with promotion of women's rights, a connection orientalists never made. Yet the regional circuits of intellectual life evident under the protectorate persisted after independence, raising questions about the tenability of the new version of national Islam.